Correlation analysis of serum Fractalkine and AHO3 levels with the prognosis of acute cerebral infarction patients after intravenous thrombolysis: Serum Fractalkine and AHO3 levels in prognosis of ACI - Yun, Dong; Wang, Yu; Zuo, Peng; Deng, Shuai; Yan, Fangfang; Jin, Chai; Wang, Zhou (Journal of Medical Biochemistry, 2026)
Objective To examine the association between the prognosis of patients with acute cerebral infarction (ACI) following intravenous thrombolysis and the levels of blood AHO3 and Fractalkine.Methods A total of 322 patients with acute cerebral infarction (ACI) who underwent intravenous thrombolysis at this hospital from May 2023 to May 2025 were selected as research subjects. Based on the National Institutes of Health Stroke Scale (NIHSS) score at admission, the patients were classified into three groups: severe, moderate, and mild. Using the modified Rankin scale, the patients' prognosis was assessed throughout a 90-day follow-up period. There were two groups of patients: those with a fair prognosis and those with a poor prognosis. Patients with varying degrees of illness severity had their serum levels of AHO3 and Fractalkine compared. The relationship between the severity of ACI and the levels of serum AHO3 and Fractalkine was examined using Spearman correlation analysis. The factors predicting poor prognosis following intravenous thrombolysis in ACI patients were examined using multivariate logistic regression, and the clinical data of the groups with excellent and poor prognoses were compared. Serum levels of AHO3 and Fractalkine alone and together were analyzed using a receiver operating characteristic (ROC) curve to predict poor outcome in patients with ACI following intravenous thrombolysis.Results There were 174 patients in the mild group, 102 patients in the intermediate group, and 46 patients in the severe group. The moderate group's serum AHO3 level was lower than the mild group's (P
Keywords: Acute cerebral infarction; Intravenous thrombolysis; Prognostic factors; Predictive value